(untitled) (Journal of Universal Science Research, 2023)
The Kashkadarya oasis is was important part of the Bukhara Emirate, and the cities of the oasis played an important role in the socio-political, economic and cultural life of the emirate. One of such important areas is the last medieval Kitab principality, which is covered in this article about its historical-geography, history, socio-economic and political history, on the basis of scientific sources and memoirs and diaries of Russian tourists.